Business Incubation Based on Technopreneurship Learning Factory: Model Design and Expert Perspectives - Indriaturrahmi, Indriaturrahmi; Prayogi, Saiful; Gummah, Syifa'ul (International Journal of Essential Competencies in Education, 2024)
This study aims to design and validate a business incubation model based on a technopreneurship learning factory, addressing the gap between academic learning and industry demands in the context of Industry 4.0. The increasing unemployment rate among university graduates, exacerbated by a lack of practical skills and industry alignment, highlights the urgency for innovative educational approaches. The proposed model integrates theoretical knowledge with entrepreneurial simulations, fostering design thinking and competitive advantage in technopreneurship. Employing a developmental research approach, the model was evaluated through expert validation involving specialists in education, business, and technology. The validation process emphasized content and construct validity, ensuring the model's alignment with both academic and industrial requirements. The results confirmed its theoretical soundness and practical relevance, marking a significant step in revitalizing entrepreneurship education programs. This model provides a framework for universities to bridge the skills gap and enhance their role in preparing students for the modern labor market. Future research should focus on piloting the model across diverse disciplines and institutions to assess its adaptability and long-term impact. By fostering industry-academic collaboration, this study contributes to the development of a sustainable technopreneurship ecosystem, advancing innovation while addressing the challenges of traditional entrepreneurship education.